Peer review of the pesticide risk assessment for the active substance bromoxynil in light of negligible exposure data submitted. (13th December 2018) - ; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Brancato, Alba; Brocca, Daniela; Bura, Laszlo; Carrasco Cabrera, Luis; Chiusolo, Arianna; Civitella, Consuelo; Court Marques, Daniele; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State France for the pesticide active substance bromoxynil are reported. The European Commission requested EFSA to conduct a peer review and provide its conclusions on whether exposure of humans to bromoxynil can be considered negligible, taking into account the European Commission's draft guidance on this topic. The conclusions were reached on the basis of the evaluation of the representative uses of bromoxynil as a herbicide on maize and straw cereals. The reliable endpoints, derived from the studies and the literature data presented in the dossier and considered appropriate for use in regulatory risk assessment, are presented.